Silencing CCL8 inhibited the proliferation and migration of PDGF-BB-stimulated human aortic smooth muscle cells. Issue 8 (2nd August 2020) - Dai, Shipeng; Zhang, Jiangang; Xu, Zesheng
ABSTRACT: C-C motif Chemokine ligand 8 (CCL8) has been found in diseases' pathogenesis. But its molecular mechanism in atherosclerosis (AS) remains to be elucidated. Human aortic smooth muscle cells (HASMCs) were stimulated by PDGF-BB to establish cell model. α-SMA in PDGF-BB-stimulated HASMCs was measured by immunofluorescence staining. Relative gene expressions in PDGF-BB-stimulated HASMCs were detected by quantitative real-time polymerase chain reaction and western blot. HASMCs proliferation, migration, and cell cycle were assessed by cell counting kit-8, wound-healing assay, and flow cytometry. HASMCs viability was increased after PDGF-BB stimulation, with α-SMA downregulation yet CCL8 upregulation. Silencing CCL8 inhibited PDGF-BB-stimulated HASMCs proliferation and migration, and increased cells percentage in G1 phases but decreased those in S phase. Also, silencing CCL8 decreased OPN and cyclinD1 expressions and AKT and ERK1/2 phosphorylation while increased those of α-SMA and Sm22α. However, upregulating CCL8 led to opposite effects, suggesting CCL8 could be an atherosclerosis therapeutic target. GRAPHICAL ABSTRACT: uf0001 Silencing CCL8 inhibited the proliferation and migration of PDGF-BB-stimulated human aortic smooth muscle cells.